Empowering Community Health Workers to Collect and Record Maternal and Child Health Data by Resolving Contradictions - Ngoma, Caroline; Igira, Faraja Teddy (Journal of Health Informatics in Africa, 2015)
Background and Purpose: It was noted that traditional birth attendants, village health workers and health facility workers to a substantial extent failed at collecting and recording maternal and child health data in the community.Methods: This is a qualitative study and data was collected using interviews, observations, participant observations, focus groups and document reviews. To analyse the data, we used the concept of contradictions from the Cultural Historical Activity Theory (CHAT) as an analytical tool to understand manifestations of contradictions that hindered collection and recording of the data.Results: Based on the analysis, results indicate that, traditional birth attendants and village health workers were empowered to adapt new information practices, which led to improvements in recording and reporting of births, follow-up on pregnant women and an increase of referred women for deliveries to the health center.Conclusions: This study demonstrates that traditional birth attendants and village health workers’ information practices can be changed through understanding and resolving manifestations of contradiction that hinder them to collect and record maternal and child health data. This study also indicates that, traditional birth attendants and village health workers should be empowered to improve their performance and confidence in capturing and communicating these data.Keywords: Information practices, Empowerment, Transformation, Community health workers, Contradictions.